Quality of sports physical fitness extracurricular participants - Satrio, Bimo; Winarno, Mashuri Eko (Universitas Nusantara PGRI Kediri, 2019)
This study aims to determine the condition of lung cardiac endurance (VO2 Max) of sports extracurricular participants at SMA Negeri 8 Malang. The research method used was descriptive quantitative with the research subjects of sports extracurricular participants of SMA Negeri 8 Malang numbering to 107 students; 32 students of basketball, 26 students of badminton, 21 students of volleyball, and 28 students of Soccer or futsal. The instrument used was a multistage fitness test with a descriptive quantitative percentage data analysis. The results of the study showed that male members of basketball and futsal had an average VO2 Max between 35.0-38.3 ml/kg/ minute, while badminton and volleyball members had an average VO2 Max less than 35.0 ml/kg/ minute. For the female groups of basketball, volleyball and futsal members, they had an average VO2 Max between 31.0-34.9 ml/kg/ minute, while badminton members had an average VO2 Max between 25.0-30.9 ml/kg/ minute. The conclusions were that male members of basketball and futsal were in the category of